Creating shared value: the case of innovability at Suzano in Brazil (INMR - Innovation & Management Review, 2022)
Purpose – This study aims to investigate how Suzano implemented shared value (SV) strategies to reconcileprofitability and social welfare by joining innovation and sustainability.Design/methodology/approach – The authors use an exploratory, descriptive qualitative approach usingthe interactive qualitative analysis (IQA) method. IQA procedures and protocols were operationalized to get toSuzano’s SV system. Primary data were collected through in-depth interviews. Content analyses wereconducted with the support of Atlas.ti software.Findings – The most relevant findings of this research are (1) Suzano developed a unique strategy to spreadcollaborative and innovation mindset throughout the organization called “innovability”; (2) Suzano’s effort tounderstand local community’s demands and a collaborative work raised the companies’ profitability andenabled prosperity for the community; (3) the IQA procedures and protocols enabled the development of aSuzano’s SV system, composed of nine elements and their relationships. They are purpose-driven leadership,materiality matrix, social welfare, profitability, ecosystem, business results, social results, impact andsustainable economic development, (4) purpose-driven leadership is the system’s driver.Research limitations/implications – This study was limited to studying the implementation of the SV as astrategy to reconcile profitability and welfare. Despite the findings about the company’s conflicts with localcommunities and the strategy with small family producers, other studies could evaluate the strategy ofdifferent stakeholders, such as the supply chain since Suzano is one of the leading companies of paper sales inBrazil.Practical implications – By using IQA protocols and the nine elements of this study, other researchers mayreplicate it to investigate the adoption of SV strategies in other organizations. The SV system developed in thisstudy may be used by business leaders to disseminate the SV policies and practices in their organization.Social implications – The company adopts the three forms of SV -reconceiving products and markets,redefining productivity in the value chain and developing clusters with the local community-as strategies forsustainable and collaborative management. Suzano was led to get involved with the problems and conflicts’root causes. By doing so, the company unlocked innovation as a driver to achieve sustainable and responsiblemanagement. For them, innovation is in service of sustainability, creating innovability. Both concepts are partof the whole organization culture and practice. Innovability is Suzano’s essence, and SV strategies are themeans to scale it.Originality/value – The originality of the paper relies on the method and techniques used to gather andanalyze primary data, in which the unit of analysis (Suzano’s SV strategy) was considered a system. Majorfindings were validated with research participants. By using IQA protocols and the nine elements of this study,other researchers may replicate it to investigate the adoption of SV strategies in other organizations.